Transcribing and annotating speech corpora for speech recognition: A three-step crowdsourcing approach with quality control - Hämäläinen, A.; Moreira, F. P.; Avelar, J.; Braga, D.; Dias, M. S. (Proceedings of the 1st AAAI Conference on Human Computation and Crowdsourcing, HCOMP 2013, 2013)
Large speech corpora with word-level transcriptions annotated for noises and disfluent speech are necessary for training automatic speech recognisers. Crowdsourcing is a lower-cost, faster-turnaround, highly scalable alternative for expert transcription and annotation. In this paper, we showcase our three-step crowdsourcing approach motivated by the importance of accurate transcriptions and annotations.